The influence of immune individuals in disease spread evaluated by cellular automaton and genetic algorithm. (November 2020) - Monteiro, L.H.A.; Gandini, D.M.; Schimit, P.H.T.
Highlights: It is conjectured that immune individuals affect the spread of contagious diseases. An epidemic model formulated in terms of cellular automaton is proposed. Genetic algorithm is employed to identify three parameters of this model. Data of varicella prevalence in Belgium and Italy around the year 2000 are used. The actual role of immune individuals in infection spread is discussed. Abstract: Background and objective: One of the main goals of epidemiological studies is to build models capable of forecasting the prevalence of a contagious disease, in order to propose public health policies for combating its propagation. Here, the aim is to evaluate the influence of immune individuals in the processes of contagion and recovery from varicella. This influence is usually neglected. Methods: An epidemic model based on probabilistic cellular automaton is introduced. By using a genetic algorithm, the values of three parameters of this model are determined from data of prevalence of varicella in Belgium and Italy, in a pre-vaccination period. Results: This methodology can predict the varicella prevalence (with average relative error of 2 % − 4 % ) in these two European countries. Belgium data can be explained by ignoring the role of immune individuals in the infection propagation; however, Italy data can be explained by considering contagion exclusively mediated by immune individuals. Conclusions: The role of immune individuals should be accurately delineated in investigations on the dynamics of disease propagation. In addition, the proposed methodology can be adapted for evaluating, for instance, the role of asymptomatic carriers in the novel coronavirus spread.